2023
DOI: 10.1080/16549716.2023.2202465
|View full text |Cite
|
Sign up to set email alerts
|

What to scale first? A cross-sectional analysis of factors affecting cesarean delivery rates at first referral units in Bihar, India

Abstract: Background Low rates of caesarean delivery (CD) (<10%) hinder access to a lifesaving procedure for the most vulnerable populations in low-resource settings, but there is a paucity of data regarding which factors contribute most to CD rates. Objectives We aimed to determine caesarean delivery rates at Bihar’s first referral units (FRUs) stratified by facility level (regional, sub-district, district). The secondary aim was to identify facility-level factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This is in contrast to studies which do not assess the role of multiple transfusions to an individual patient, some of which might be ABO identical and some not, and therefore could not assess the overall clinical outcomes following ABO identical transfusions. 2 More problematic are studies that claim to find no benefit of ABO identical platelet transfusions, which include patients in the ABO identical group based solely upon a patient's first transfusion, and then ignoring subsequent, perhaps numerous ABO nonidentical transfusions. 3,4 This is concerning as it makes no scientific sense to include in the ABO identical group a patient who received a first ABO identical platelet transfusion and then received one or more ABO nonidentical transfusions.…”
Section: In Response: Abo Nonidentical Platelet Transfusions and Mort...mentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast to studies which do not assess the role of multiple transfusions to an individual patient, some of which might be ABO identical and some not, and therefore could not assess the overall clinical outcomes following ABO identical transfusions. 2 More problematic are studies that claim to find no benefit of ABO identical platelet transfusions, which include patients in the ABO identical group based solely upon a patient's first transfusion, and then ignoring subsequent, perhaps numerous ABO nonidentical transfusions. 3,4 This is concerning as it makes no scientific sense to include in the ABO identical group a patient who received a first ABO identical platelet transfusion and then received one or more ABO nonidentical transfusions.…”
Section: In Response: Abo Nonidentical Platelet Transfusions and Mort...mentioning
confidence: 99%
“…Using open-source national datasets, the study included 149 government-owned secondary healthcare facilities known as first referral units (FRUs) in Bihar, from April 2018 to March 2019. 2 The study found that the state-wide FRU cesarean delivery (CD) rate was 3.1%, well below state, nationally, and internationally recommended CD rates. 2 A functioning operating room and availability of obstetriciangynecologists and other providers trained in emergency obstetric care were positively associated with facility-level CD rates.…”
mentioning
confidence: 98%
See 1 more Smart Citation